High-Yield Synthesis of Silver Nanoparticles by Precipitation in a High-Aqueous Phase Content Reverse Microemulsion. (28th March 2010) - Sosa, Y. D.; Rabelero, M.; Treviño, M. E.; Saade, H.; López, R. G.
Abstract : Silver nanoparticles were precipitated at 70 ° C in a reverse microemulsion containing a high concentration of 0.5 M silver nitrate aqueous solution, toluene as organic phase, and a mixture of surfactants sodium bis (2-ethylhexyl) sulfosuccinate/sodium dodecyl sulfate (2/1, w/w). Nanoparticles were characterized by X-ray diffraction, atomic absorption spectroscopy, and high-resolution transmission electron microscopy. In spite of the high-water/surfactant molar ratio and concentration of silver nitrate solution used in this study, characterizations demonstrated that nanoparticles were silver crystals (purity >99%) with 8.6–8.8 nm in average diameter and 2.9–4.7 nm in standard deviation. It is proposed that slow dosing rate of aqueous solution of precipitating agent and the small molecular volume of toluene attenuated both particle aggregation and polydispersity widening. Experimental yield of silver nanoparticles obtained in this study was much higher than theoretical yields calculated from available data in the literature on preparation of silver nanoparticles in reverse microemulsions.